Ultrasound-Guided Axillary Brachial Plexus Block as a Definitive Anesthetic Strategy in a Patient with Anticipated Difficult Airway Following Post-Burn Cervical Flap Reconstruction: A Case Report - Muhammad Husni Thamrin; Muhammad Ridho Aditya; Irfan Yuananda (HM Publisher, 2026)
Introduction: Airway management in patients with post-burn cervical flap reconstruction is challenging because hypertrophic scars, restricted neck mobility and limited mouth opening compromise both ventilation and laryngoscopy. Ultrasound-guided regional anesthesia is increasingly proposed as an alternative that preserves spontaneous ventilation and avoids airway instrumentation entirely. Case presentation: A 47-year-old woman scheduled for bilateral hand contracture release presented with extensive post-burn cervical flap reconstruction performed 15 years earlier, persistent neck contractures, facial scarring, Mallampati class III, limited inter-incisor distance and markedly reduced cervical extension. Routine laboratory and chest radiographic findings were within normal limits. An ultrasound-guided axillary brachial plexus block was selected as the sole anesthetic technique, using 20 mL of 2% lidocaine delivered in-plane around the median, ulnar, radial and musculocutaneous nerves. A complete sensorimotor block was achieved within 15 minutes. The procedure proceeded uneventfully without conversion to general anesthesia, and the patient remained hemodynamically stable with effective postoperative analgesia and no neurological deficit. Conclusion: Ultrasound-guided axillary brachial plexus block can serve as a safe and effective definitive anesthetic strategy for distal upper-limb surgery in post-burn cervical flap patients with anticipated difficult airway, supporting the principle that distance from the airway is itself a deliberate anesthetic plan.